The Centro de Estudios sore la Memoria Educativa (CEME) of the University of Murcia and the research in the History of Mathematical Education - Carrillo Gallego, Dolores; Moreno Martínez, Pedro Luis; Sánchez Jiménez, Encarna (Historia y Memoria de la Educación, 2019)
The CEME was created in 2009 with the aim of promoting the preservation, study and dissemination of the memory and historical-educational heritage of educational institutions in the Región de Murcia, as is explained on the CEME website (www.um.es/web/ceme). Its structure brings together professors from the University of Murcia belonging to different areas of knowledge, mainly relating to the History of Education and, more specifically, to Didactics. This document presents the objectives and achievements of CEME, especially those related to its research programme. One of the CEME groups comes from the field of Didactics of Mathematics, and its research interests are oriented towards the History of Mathematical Education (known in Spanish as HEM). An objective of this document is to present some of the work carried out so far, evaluating the contribution of CEME to its research and describing the lines of action that this group is developing in the field of HEM.